Exploring the Social-Economic Approach on the Production Level of Rice: Panel Data Analysis from 34 Province in Indonesia - Fitty Valdi ARIE; Adrian Szilard NAGY; Dhita Widya PUTRI (SEA: Practical Application of Science)
The social-economic approach in rice production emphasizes the importance of understanding and solving social and economic problems related to the agricultural sector. The Ongoing economic changes, competition for resources from other sectors, environmental changes and the increasing commercialization of rice farming mean that the way rice is produced in the future will be very different. The aim of this research is to determine the influence of the relationship between rice productivity and economic indicators on maintaining sustainable food security. This research uses the HDI variable instrument as an intervening variable using panel data from 34 provinces in Indonesia in 2018-2023, which was tested using the REM, CEM, and FEM models. It is known that simultaneously, economic indicators, namely land area, productivity, inflation, poverty index, rice consumption, and population, have an effect on the amount of rice production; however, in partial testing through sub structural model 1 testing, it was found that productivity and rice consumption had no impact on the intervening variables HDI and sub structural test 2 found that partial inflation, poverty index, rice consumption, and population had no effect on the amount of rice production. Despite a series of tests, the results remained consistent. In the future, it is necessary to develop a new vision for rice farming, such as exploring food security and technology, and drafting strategic policy reforms, considering global trends and the unstable economic scenario.